Emotional Weariness Mediates the Impact of Toxic Leadership on Workplace Misbehavior, Whereas Organizational Cynicism Modifies it - Ebtissam Mohammad Rashid Albaqawi; Murooj Yousef Nazeer; Hadiah Ashowi Alanzi; Fahad Nasser Alharbi; Suaad Hassan Alzahrani; Samia Daham Alqaseem; Khdeja Ibrahim Asiri (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Toxic leadership is a pervasive issue in nursing environments, characterized by harmful behaviors such as abusive communication, lack of empathy, and micromanagement, which contribute to workplace deviance. Workplace deviance negatively impacts nurse well-being, leading to emotional exhaustion and undermining organizational performance. This study explores the role of Emotional weariness mediates the impact of toxic leadership on workplace misbehavior, whereas organizational cynicism modifies it. Methods: A research was adopted , including 243 nurses selected through quota sampling. Data were collected using well-established scales to assess toxic leadership, emotional exhaustion, workplace deviance, and organizational cynicism. Statistical analysis involved path analysis using Process for mediation, hierarchical regression for moderation, and linear regression to predict workplace deviance. Results: The study found significant positive relationships between toxic leadership and workplace deviance (β = 0.52, p < 0.001), with emotional exhaustion mediating this relationship (indirect effect = 0.38, p < 0.001). Organizational cynicism was found to moderate the toxic leadership-workplace deviance link, with higher cynicism intensifying the impact of toxic leadership (β = 0.31, p < 0.01). Additionally, high toxic leadership, emotional exhaustion, and organizational cynicism together led to the highest levels of workplace deviance. Conclusion: Toxic leadership significantly contributes to workplace deviance among nurses, with emotional exhaustion acting as a key mediator and organizational cynicism enhancing the negative effects. Interventions aimed at reducing toxic leadership behaviors and addressing emotional exhaustion and organizational cynicism are critical to improving nurse well-being and organizational outcomes.